2015
DOI: 10.1111/apm.12382
|View full text |Cite
|
Sign up to set email alerts
|

Fibular giant cell-rich osteosarcoma virtually indistinguishable radiographically and histopathologically from giant cell tumor-analysis of subtle differentiating features

Abstract: Giant cell-rich osteosarcoma by its abundance of osteoclastic giant cells and paucity of tumor osteoid, leads to its easy confusion with giant cell tumor during biopsy interpretation. In this report, we describe a unique case of upper fibular metaphyseal giant cell-rich osteosarcoma in a 12-year-old boy; the radiographic and histopathologic features of the biopsy and initial resected tumor are virtually indistinguishable from conventional giant cell tumor. The tumor rapidly recurred 7 months after resection wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…16 Postsurgical and radiotherapy-induced secondary malignancy are believed to have different etiologies but cannot be distinguished by radiographic and histologic presentation. 14 Giant cell-rich osteosarcoma is characterized by an abundance of osteoclast-like giant cells and lack of tumor osteoid, which can be misdiagnosed as GCTB; 52 similar to GCTB, it also occurs at epiphyses. 52 Bertoni and colleagues suggested that the clinical importance of differentiating primary malignant GCTB from giant cell-rich osteosarcoma may be limited, but the need to differentiate both diseases from benign GCTB is complicated by the subtlety of pathologic evidence of malignancy (Table 5).…”
Section: Challenges Associated With Diagnosis Of Malignant Gctbmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Postsurgical and radiotherapy-induced secondary malignancy are believed to have different etiologies but cannot be distinguished by radiographic and histologic presentation. 14 Giant cell-rich osteosarcoma is characterized by an abundance of osteoclast-like giant cells and lack of tumor osteoid, which can be misdiagnosed as GCTB; 52 similar to GCTB, it also occurs at epiphyses. 52 Bertoni and colleagues suggested that the clinical importance of differentiating primary malignant GCTB from giant cell-rich osteosarcoma may be limited, but the need to differentiate both diseases from benign GCTB is complicated by the subtlety of pathologic evidence of malignancy (Table 5).…”
Section: Challenges Associated With Diagnosis Of Malignant Gctbmentioning
confidence: 99%
“…Alternatively, it could reflect another challenge known to be associated with primary malignant GCTB, in that many diagnoses are missed. 8,52 Complementary to pathologic evaluation in GCTB diagnosis is radiology. Bertoni and colleagues reported that primary malignant cases (and certain secondary malignant cases) were impossible to distinguish from benign lesions on plain films, and computerized tomography (CT)/magnetic resonance imaging (MRI) data were often unavailable.…”
Section: Challenges Associated With Diagnosis Of Malignant Gctbmentioning
confidence: 99%
“…13 However, differentiating a GCTB from the giant cell-rich variant of osteosarcoma is, however, challenging because the histological features of both entities can overlap. 16 These two tumour types cannot even be distinguished by staining cytological preparations for alkaline phosphatase activity. 6 However, it should be possible to establish a diagnosis based on the absence of periosteal reaction on the radiographs and the very few atypia encountered during histological section examination.…”
Section: Discussionmentioning
confidence: 99%
“…6 However, it should be possible to establish a diagnosis based on the absence of periosteal reaction on the radiographs and the very few atypia encountered during histological section examination. 16 In humans, the immunohistochemical detection of a mutation-specific antibody directed against one particular mutant has also demonstrated high specificity and sensitivity for the diagnosis of GCTBs. 17 If the cortices are not affected by osteolysis, and when sufficient intact subchondral bone is present, an additional imaging examination is not required.…”
Section: Discussionmentioning
confidence: 99%
“…Most cases of giant cell-rich osteosarcoma have been reported in the long bones of extremities. 1,[3][4][5][6][7][8][9] Rare locations previously described include the maxilla, mandible, and bladder. 2,[10][11][12] To the best of our knowledge, giant cell-rich osteosarcoma of the parotid gland has never been reported in the literature.…”
mentioning
confidence: 99%